Analysis of Plasmodium vivax schizont transcriptomes from field isolates reveals heterogeneity of expression of genes involved in host-parasite interactions - Siegel, SV; Chappell, L; Hostetler, JB; Amaratunga, C; Suon, S; Böhme, U; Berriman, M; Fairhurst, RM; Rayner, JC (Nature Research, 2020)
Plasmodium vivax gene regulation remains difficult to study due to the lack of a robust in vitro culture method, low parasite densities in peripheral circulation and asynchronous parasite development. We adapted an RNA-seq protocol "DAFT-seq" to sequence the transcriptome of four P. vivax field isolates that were cultured for a short period ex vivo before using a density gradient for schizont enrichment. Transcription was detected from 78% of the PvP01 reference genome, despite being schizont-enriched samples. This extensive data was used to define thousands of 5' and 3' untranslated regions, some of which overlapped with neighbouring transcripts, and to improve the gene models of 352 genes, including identifying 20 novel gene transcripts. This dataset has also significantly increased the known amount of heterogeneity between P. vivax schizont transcriptomes from individual patients. The majority of genes found to be differentially expressed between the isolates lack Plasmodium falciparum homologs and are predicted to be involved in host-parasite interactions, with an enrichment in reticulocyte binding proteins, merozoite surface proteins and exported proteins with unknown function. An improved understanding of the diversity within P. vivax transcriptomes will be essential for the prioritisation of novel vaccine targets.